Каникулы оборотней: роман / Андрей Белянин, Галина Черная - Белянин Андрей Олегович (Армада, 2004)
Экземпляры: ф30 (20241227) / Инвентарный номер: 37706 / Цена: 54.00 / Сис.шифр: Р2 / Авт.знак: Б 44 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6